Directional Dependence Orders of Random Vectors - Enrique de Amo; María del Rosario Rodríguez-Griñolo; Manuel Úbeda-Flores (Mathematics, 2024)
In this paper, we define a multivariate order based on the concept of orthant directional dependence and study some of its properties. The relationships with other dependence orders given in the literature are also studied. We analyze the order between two random vectors in terms of their associated copulas and illustrate our results with several examples.